Investigation of mode III fracture behaviour in bonded pultruded GFRP composite joints. (1st March 2017) - Cricrì, G.; Perrella, M.
Abstract: In this work, a numerical-experimental characterization of pure mode III fracture toughness of bonded pultruded fibreglass composite joints is presented. Three types of specimen were considered, which differ for the fibres orientation of the bonded surfaces. The analysed angular orientations are: parallel (0 °–0 °), inclined (0 °–45 °), and perpendicular (0 °–90 °). The experimental investigation was realized by using the recently proposed torque shells test (TST). Numerical analyses, based on Finite Element Method (FEM), were performed in order to model a cohesive law of the adhesive interface. A minimization algorithm was also used for identification of cohesive zone model (CZM) parameters by comparing numerical and experimental outcomes. The results show how the TST provides with an almost pure mode III fracture loading condition when the adherends are non-isotropic materials. The comparison of experimental and numerical torque-angle curves, for every test case, shows a satisfactory agreement. As a result of the analyses, the influence of fibres direction on the mode III fracture behaviour of pultruded GFRP joints can be considered negligible for practical applications.